Supporting circular economy innovation: An analysis of a circular economy intervention in Wales - Gary Walpole; Peter Treadwell; Laura Steffes; Emily Bacon; Nick Clifton (Welsh Economic Review (WER), 2024)
The Intergovernmental Panel on Climate Change (IPCC) recently advised that "climate change is a grave and mounting threat to our wellbeing and a healthy planet" (2023, p.6). This threat underlines the importance of developing businesses innovation capabilities and implementing Circular Economy (CE) principles. Organisations that have developed innovation capabilities are most likely to implement CE principles within their organisations. However, the UK has suffered a 'long tail of productivity' largely due to the UK's relatively low levels of innovation across the firm population. In Wales, the location of this study, output per hour worked was almost 16% below the UK average in 2021, suggesting that the levels of innovation capability might hinder CE implementation. Therefore, evidence on programmes that support organisations to develop their innovation capabilities and their CE understanding should be of interest to policymakers, academics, and practitioners. This paper presents data collected from a university designed CE innovation programme, the Cardiff Circular Economy Network, and suggests that the novel approach adopted enhanced the innovation capabilities and CE knowledge of participants.
Keywords: 330